2010
DOI: 10.1177/1545968310372138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Arm Cycling Following Botulinum Toxin Injection for Poststroke Spasticity: Evidence From fMRI

Abstract: Increased activity in SII of the contralesional hemisphere and in MISI of the lesioned hemisphere reflect a treatment-induced effect in the paretic arm. It is hypothesized that the increased BOLD activity results from increased afferent information related to the antispastic BTX effect reinforced by training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…This clinical improvement expressed in MAS scores was associated with partial reduction of active network volume in most of the observed areas. This trend agrees with findings in our previous pilot studies and other recent studies focused on fMRI cerebral changes after BoNT-A application in stroke patients [19][20][21][22]. A notable exception to this trend regards the cerebellar hemispheres, which either appear similarly active across the three imaging sessions (ipsilesional) or manifest transient activation at the time of maximal BoNT-A effect (contralesional).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This clinical improvement expressed in MAS scores was associated with partial reduction of active network volume in most of the observed areas. This trend agrees with findings in our previous pilot studies and other recent studies focused on fMRI cerebral changes after BoNT-A application in stroke patients [19][20][21][22]. A notable exception to this trend regards the cerebellar hemispheres, which either appear similarly active across the three imaging sessions (ipsilesional) or manifest transient activation at the time of maximal BoNT-A effect (contralesional).…”
Section: Discussionsupporting
confidence: 91%
“…Most of previous fMRI studies in stroke patients have described changes in task-related cortical activity following physiotherapy treatment, e.g., constraint-induced therapy [18]. Only several studies reported cortical changes after BoNT-A injections into the spastic muscles [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Other positive effects of modified afferent information after BoNT A on cerebral activity have been found in poststroke patients. 32 The 16% decrease in the voluntary torque produced by activation of the quadriceps is lower than the values found in the literature 6 (−40% in the flexor digitorum of poststroke patients). This can be explained by the fact that RF is only a part of the quadriceps and is probably not the primary portion in terms of strength.…”
Section: Discussionmentioning
confidence: 58%
“…There is also structural and functional reorganization of the supratentorial networks; however, the specific motor behavior-related characteristics of the reorganization are poorly understood. Functional imaging studies described brain activation patterns during passive movement of spastic limb [1619], but there have been no studies that characterized spasticity-related features during active functional motor tasks. Furthermore, a few studies described changes in brain activation following neuromuscular blockade treatment of hypertonicity [16, 2023], but it is unknown which changes in brain activation occur in relationship to mitigation of spasticity as result of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional imaging studies described brain activation patterns during passive movement of spastic limb [1619], but there have been no studies that characterized spasticity-related features during active functional motor tasks. Furthermore, a few studies described changes in brain activation following neuromuscular blockade treatment of hypertonicity [16, 2023], but it is unknown which changes in brain activation occur in relationship to mitigation of spasticity as result of rehabilitation. Overall, there has been no characterization of the functional brain changes associated with volitional movement-related spasticity caused by stroke or recovery of spasticity in response to rehabilitation.…”
Section: Introductionmentioning
confidence: 99%